Empirical Equation between Predominant Frequency and Sediment Thickness in Plampang, West Nusa Tenggara - Iswanto, Eko Rudi; Riyanto, Theo Alvin; Suntoko, Hadi (EKSPLORIUM, 2023)
Soil characteristics mapping is one of the essential aspects in the development of a region. Soil characteristics such as the predominant frequency and thickness of the sediment layer are needed to ensure the capacity of soil against the load of an infrastructure construction. The existence of tectonic activity causes West Nusa Tenggara Province to be an area with high seismic activity. Along with the plan to accelerate the development of the Samota Area, seismic studies are one of the aspects that determine project feasibility. The predominant frequency value from the results of microtremor measurements is used in the development of an empirical formula to predict soil thickness in the Plampang area. The empirical formula from previous research is used as a conformity test of the empirical formula obtained. Empirical equations are then used to map variations in sediment thickness in the Plampang area, which are justified based on geological data. The results of the sediment thickness map based on the empirical formula for the Plampang area showed a good correlation with the predominant frequency and also showed a good correlation with the results of the formula that has been carried out by previous studies.